Paraneoplastic Pemphigus Associated with Follicular Dendritic Cell Tumor in the Mediastinum - Aparna Mullangath Prakasan; Anne Jennifer Prabhu; Kanmani Velarasan; Selvamani Backianathan; Thomas Samuel Ram (Case Reports in Dermatological Medicine)
Paraneoplastic Pemphigus (PNP) is an autoimmune bullous disease characterized by severe stomatitis, polymorphous skin eruptions, and underlying neoplasms. Diagnosis of cutaneous paraneoplastic disorders requires high index of suspicion. We describe a patient with PNP associated with follicular dendritic cell (FDC) tumor in the mediastinum, a rare neoplasm originating from follicular dendritic cells. Its management requires identification of underlying malignancy and treatment of the same. Our patient showed remission of PNP upon excision of the tumor and remained disease-free for 8 years.